A new concept of multi electron-hole pair generation using dark-bright soliton conversion control - Punthawanunt, S.; Teeka, C.; Jomtarak, R.; Mitatha, S.; Ali, J.; Yupapin, P. P. (My University, 2011)
In this paper, we have derived and presented a new concept of multi electron-hole pair generation by using dark-bright soliton collision within the modified add/drop filter, which it is known as PANDA ring resonator. By using the dark-bright soliton conversion control, the obtained outputs of the dynamic states can be used to form the multi electron-hole pair, which can be available for communication security application. © 2011 American Institute of Physics.
Keywords: Optical soliton; Optical waveguides; Resonators